2014
DOI: 10.1016/j.bpj.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Reaction-Diffusion Model of Tau-Microtubule Dynamics and Its Application in FDAP Analysis

Abstract: Fluorescence decay after photoactivation (FDAP) and fluorescence recovery after photobleaching (FRAP) are well established approaches for studying the interaction of the microtubule (MT)-associated protein tau with MTs in neuronal cells. Previous interpretations of FDAP/FRAP data have revealed dwell times of tau on MTs in the range of several seconds. However, this is difficult to reconcile with a dwell time recently measured by single-molecule analysis in neuronal processes that was shorter by two orders of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…Based on the effective diffusion constants, Ͼ90% of the constructs were bound to microtubules, which is consistent with previous data on the tau-MT interaction in processes of living cells (16,32). To directly estimate the pseudo-first-order association rate (k* on ϭ k on [MT] eq , where [MT] eq is the equilibrium concentration of tau-binding sites on MTs) and the dissociation rate (k off ), we used a previously developed refined reaction-diffusion model of the tau-MT interaction (33). Absence of E1 led to a moderate but significant increase in k* on but did not influence k off (Fig.…”
Section: Annexin-tau Interactionsupporting
confidence: 77%
See 1 more Smart Citation
“…Based on the effective diffusion constants, Ͼ90% of the constructs were bound to microtubules, which is consistent with previous data on the tau-MT interaction in processes of living cells (16,32). To directly estimate the pseudo-first-order association rate (k* on ϭ k on [MT] eq , where [MT] eq is the equilibrium concentration of tau-binding sites on MTs) and the dissociation rate (k off ), we used a previously developed refined reaction-diffusion model of the tau-MT interaction (33). Absence of E1 led to a moderate but significant increase in k* on but did not influence k off (Fig.…”
Section: Annexin-tau Interactionsupporting
confidence: 77%
“…The microscope was enclosed in an incubation chamber maintained at 37°C and 5% CO 2 (Solent Scientific, Fareham, UK). Photoactivation of a neurite's segment 6 m in length and automated image acquisition of 112 frames after photoactivation with a frame rate of 1/s were performed as described previously (33). Analysis of individual FDAP curves to estimate directly the pseudo-first-order association rate (k * on ) and the dissociation rate (k off ) of tau to/from microtubules was performed as described previously (32).…”
Section: Live Imaging and Fdap Analysis Of Tau-microtubule Interactionmentioning
confidence: 99%
“…The data showed that tau-microtubule dynamics differ in vitro and in vivo. In particular, it was shown that diffusion of bound tau was negligible in vivo contrary to the findings that tau diffuses along MT lattice in vitro [19].…”
Section: Introductionmentioning
confidence: 74%
“…Deeper insight into the tau-microtubule interactions have also been provided by FDAP analysis [19]. The data showed that tau-microtubule dynamics differ in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…There was a discussion on new methods for discerning the levels of free tubulin relative to microtubules in the axons of cultured neuronal cells (Igaev et al 2014), as well as discussion on how a straightforward drug approach could be used to quantify the levels of stable and labile microtubule mass.…”
Section: Extended Meeting Reportmentioning
confidence: 99%